Proteomic analysis of the cell cycle of procylic form Trypanosoma brucei - Crozier, TWM; Tinti, M; Wheeler, RJ; Ly, T; Ferguson, MAJ; Lamond, AI (American Society for Biochemistry and Molecular Biology, 2018)
We describe a single-step centrifugal elutriation method to produce synchronous G1-phase procyclic trypanosomes at a scale amenable for proteomic analysis of the cell cycle. Using ten-plex tandem mass tag (TMT) labelling and mass spectrometry (MS)-based proteomics technology, the expression levels of 5,325 proteins were quantified across the cell cycle in this parasite. Of these, 384 proteins were classified as cell-cycle regulated and subdivided into nine clusters with distinct temporal regulation. These groups included many known cell cycle regulators in trypanosomes, which validates the approach. In addition, we identify 40 novel cell cycle regulated proteins that are essential for trypanosome survival and thus represent potential future drug targets for the prevention of trypanosomiasis. Through cross-comparison to the TrypTag endogenous tagging microscopy database, we were able to validate the cell-cycle regulated patterns of expression for many of the proteins of unknown function detected in our proteomic analysis. A convenient interface to access and interrogate these data is also presented, providing a useful resource for the scientific community. Data are available via ProteomeXchange with identifier PXD008741.